Exploring the Construction Dilemmas and Pathways of the Ningxia Yellow River Culture Study Tour Education Space - Jing Wang (Education Research on Study Tours and Practice, 2026)
The Yellow River flows through the entire territory of Ningxia, making the Ningxia Yellow River culture study tour practice typical. Therefore, by discovering and solving the practical dilemmas faced by the construction of the Ningxia Yellow River study tour education space and proposing targeted construction pathways and strategies, this study aims to provide a reference for the deepening development of study tour curricula and the integrated utilization of resources within the region, thereby enhancing the cultural and ecological educational outcomes of study tour activities. This research analyzes the construction dilemmas of the Ningxia Yellow River culture study tour education space. Based on Henri Lefebvre’s production of space theory, Yi-Fu Tuan’s space and place thought, and Jan Assmann’s cultural memory theory, three construction pathways for the Ningxia Yellow River culture study tour education space are proposed: an emotional-identification spatial construction pathway based on Yi-Fu Tuan’s space and place thought; a memory-inheritance educational space construction pathway based on Jan Assmann’s cultural memory theory; and an integrated “practice-representation-experience” educational space construction pathway based on Lefebvre’s triadic dialectic theory. The aim is to promote the improvement of the theoretical system for the construction of Ningxia Yellow River study tour educational spaces and to provide certain pathway references for subsequent related activities.